Konsumsi Minuman Manis dan Kegemukan pada Mahasiswa - Angga Hardiansyah; Andi Eka Yunianto; Dyah Raysa Laksitoresmi; Ikeu Tanziha (Universitas Muhammadiyah Semarang, 2017)
The aims of this study were to analyze a habitual consumption of sweet beverages and overweight among under graduate students. The cross-sectional study was conducted at Bogor Agricultural University in December 2014. The data were collected through self-administered tested questionnaire to 383 students after explaining by enumerators. The sweet beverage consumption was measured by the frequency of the consumption of sweet beverage per week. The type of sweet beverages include sweet soda, coffee, tea, jus, milk, energy drink, electrolyte, and sport beverage. The results showed that, after adjusted for sex, the sweet beverage consumption was not significantly associated with overweight (p >0,05). This implies that the overweightamong undergraduate student in this study may associated with total calorie intake of the students.Keywords: overweight, sweet beverage, undergraduate students